The western North American forestland carbon sink: will our climate commitments go up in smoke? - Hessburg, Paul F; Kurz, Werner A; Prichard, Susan J; Smyth, Carolyn E; Daniels, Lori D; Giardina, Christian P; Phillips, Carly A; Gray, Robert W; Tiribelli, Florencia; Baron, Jennifer N; LaFlamme, Jocelyne; Roeser, Dominik (Frontiers in ecology and the environment, 2025)
Pathways to achieving net‐zero and net‐negative greenhouse‐gas (GHG) emission targets rely on land‐based contributions to carbon (C) sequestration. However, projections of future contributions neglect to consider ecosystems, climate change, legacy impacts of continental‐scale fire exclusion, forest accretion and densification, and a century or more of management. These influences predispose western North American forests (wNAFs) to severe drought impacts, large and chronic outbreaks of insect pests, and increasingly large and severe wildfires. To realistically assess contributions of future terrestrial C sinks, we must quantify the amount and configuration of stored C in wNAFs, its vulnerability to severe disturbance and climatic changes, costs and net GHG impacts of feasible transitions to conditions that can tolerate active fire, and opportunities for redirecting thinning‐derived biomass to uses that retain harvested C while reducing emissions from alternate products. Failing to adopt this broader mindset, future forest contributions to emission targets will go up in smoke.